The Yeast Role in Medical Applications - Mohamed Hussain Abdulkhair, Waleed (IntechOpen, 2018)
Biotechnology including medical applications depends on the yeast as biofermenter to produce many industrial products including pharmaceutical ones. Although yeasts are first known as useful microorganisms, some of them are identified as pathogens for plants, animals, and humans. Due to the simple cellular structure of the yeast among other microbial groups, it is used in the earliest investigations to determine the features of eukaryotic molecular biology, cell biology, and physiology. The economic income of some countries mainly depends on yeast for producing the economic products, such as France that depends on yeast for wine production. This book throws light on yeast and its important role in the medical applications.